Development of Stem Fluid E-Modules andFlood Mitigation to Improve HOTS of Students of SMKN 1 Rejang Lebong - Kiki Lucky Novalia (Pinisi Journal of Education and Management, 2022)
The STEM approach is expected to be able to develop students' abilities in connecting the concepts of physics in fluid materials to flood disaster mitigation efforts. This study aims to: (1) Describe the design, characteristics and validity of e-modules in fluid matter physics and flood mitigation using a STEM approach. (2) Analyzing the effectiveness of the application of the e-module physics of fluid materials and flood mitigation with the STEM approach to improve Students' High Order Thinking Skill (HOTS). (3) Knowing the practicality of applying e-module physics of fluid materials and flood mitigation with the STEM approach based on student responses. This study uses the ADDIE development model. The sample for the trial application of the e-module was 30 students of class X SMKN 1 Rejang Lebong who were selected using the Purposive Sampling technique. The e-module is designed using a STEM Project Based Learning (PjBL) model with the stages of reflection, research, discovery, application and communication for students of SMK Technology and Engineering Group. Based on expert validation, the e-module is very feasible to use with an average score percentage of 90.03%. The e-module received a positive response from students of 91.07% or very good. The integrated e-fluid module for flood disaster mitigation can increase students' Higher Order Thinking Skills (HOTS) with an N gain value of 0.69 medium category. Based on the results of the t-test the application of e-modules in learning provides a very significant correlation to the improvement of student learning outcomes, which is 0.83.